Planners and aging professionals collaborate for livable communities. Issue 1 (12th March 2018) - Firestone, Stephanie Krone; Keyes, Laura; Greenhouse, Esther
Abstract : Purpose: The purpose of this paper is to share the findings from a learning intervention aimed at facilitating more regular and effective collaboration across the planning and aging sectors in order to advance Livable Communities for All Ages (LCA). Design/methodology/approach: A half-day summit that convened over 250 aging sector professionals and planners. Data from these conversations, as well as a pre-event survey, post-event evaluations, and a six-month post-event follow-up survey provide the findings for the discussion. Findings: The results revealed that the participants increasingly recognized the value of cross-sector relationships to their work on LCA. Further, the success on current projects was highly attributed to the trust gained from a previous experience of aging and planning professionals working together. Research limitations/implications: Researchers relied on a purposive sample of respondents already registered to attend the Livable Communities Summit, who were likely to be somewhat knowledgeable about the topic of age-friendly planning. While not generalizable to the broader professional fields of the aging and planning sectors, the results inform on the importance of cross-sector collaboration in the context of planning communities supportive of individuals across the lifespan. Practical implications: Existing challenges to the local residents in a broad swath of areas including housing, transportation, social isolation, purpose and more, are exacerbated in a rapidly aging world that does not advance policies, practices, and built environments to make communities more livable for residents of all ages. Originality/value: The intention of this research is to contribute to the limited existing literature on collaboration between professionals in the planning and aging fields and to stimulate the increased and improved cross-sector relationships.